ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI NELAYAN DI DESA KEDONGANAN, KECAMATAN KUTA, KABUPATEN BADUNG - Dimas, Rendi; Sutrisna, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 6, Juni 2018 (pp. 1112-1351), 2018)
The purpose of this study is to determine the effect of capital, length of time to sea, the area of catching fishing production simultaneously and partially . The results Of the simultaneous analysis on the real level of ?= 5% the value of f count (19,744) > f table (2,81) show that the capital, a long time the sea, the area catching simultaneously have a significant effect on the production of fishing this condition gives the meaning that the larger the capital, a long time sea, the area of the arrest then it will add  to the production of fishing that is produuced. capital is partially no significant effect on the production of fishing because the value t count (1,330) < t table (2,0129), a long time fishing for a partial no effect significant towards the production of fishing because the value t count (-0,255) < t table (2,0129), while the area of the arrest is partially significant effect on the production of the fishermen with the value of t count (5,911) > t table (2,0129). The variable area of the arrests has the most dominant influence on the production of the fishermen in the village of kedonganan, kuta distrct, badung regency. Keywords: Production, Capital, a long time fishing , area of the arrest